Pengaruh Ukuran Perusahaan Dan Capital Intensity Terhadap Tax Avoidance : (Perusahaan Pertambangan di Bursa Efek Indonesia) - Wansu, Evinda Elen; Dura, Justita (Politeknik Ganesha Medan, 2024)
The aim of this research is to examine the effect of company size and Capital Intensity on tax avoidance of mining companies in 2019-2021. Sampling using purposive sampling technique, the number of data is 42. Types of quantitative data and secondary data. Multiple regression data analysis techniques, coefficient of determination, and hypothesis testing (t test). The results of research on firm size and Capital Intensity have no effect on tax avoidance. Big companies will not do tax evasion because they have a reputation. Fixed asset investment aims to improve the company's operations to achieve high profits.